The 'Nuer of Dinka money' and the demands of the dead: contesting the moral limits of monetised politics in South Sudan. Issue 5 (2nd September 2020) - Pendle, Naomi R.
ABSTRACT: This article critiques explanations of South Sudan's armed conflicts since 2013 that have relied on over-simplified theories of identity or monetised politics. Instead, this article explores the renegotiation of the meanings of monetary exchanges in politics and the inter-linked remaking of political identities. Warring coalitions in South Sudan have mobilised support using different notions of political communities and divergent ideas about the role of money in defining relationships. Some political communities have faced moral condemnation for their apparent willingness to form alliances in exchange for money. The article specifically discusses the emergence of the derogatory term 'Nuer weu' ('Nuer of Dinka money') among the South Sudan armed opposition. Alternatively, other political visions have presented gifts of money as a way to reinvent naturalised, kinship-based political communities, as well as social obligations of revenge and hierarchical norms of giving. The remaking of identity and the moral limits of monetary gifts in politics cannot only mobilise forces to war but also have implications for the moral limits of peace. The article ends by discussing one commander's alternative visions of how elite money in politics could be made consistent with wartime moral norms by providing salaries for the dead.